Ekstrak Kulit Buah Kakao (Theobroma cacao L.) Limbah Perkebunan Berpotensi sebagai Akarisida Alami Terhadap Caplak Boophilus microplus - Pappa, Suryadi; Jamaluddin, Abdul Wahid; Ris, Adryani (Jurnal Veteriner; Vol 21 No 4 (2020)DO - 10.19087/jveteriner.2020.21.4.611, 2020)
This study was aims to exploit the potential waste of cocoa pod (Theobroma cacao L.) as a natural acaricide in ticks (Boophilus microplus) . The study was conducted with a two-variable completely randomized design (CRD) with two repetitions. The sample does not differentiate between sex, body weight, and length of about 0.8 - 1 cm. Each 5 ticks were treated as follows: treat 1 extract of 10% cocoa pod husk; treatment 2 20% cocoa pod skin extract; treatment 3 30% cocoa pod husk extract; treatment 4 negative control; treat 5 positive controls. In the first variable the tick was treated with methanol extract, while in the second variable the ethanol extract was treated with 10%, 20%, 30% respectively, negative control and positive control. In treatment I used 25 ticks plus treatment II 25 ticks. Each treatment was repeated to avoid data bias so that a total of 100 ticks were used. The results showed that the cocoa pod husk extract had the best killing power at a concentration of 30% with methanol solvent at 6.21 hours while ethanol solvent at 5.91 hours. The use of extraction materials has not been able to compensate for the use of synthetic materials that can kill in minutes.